1996
DOI: 10.1111/j.1532-5415.1996.tb01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a Physician Recognize an Older Driver with Increased Crash Risk Potential?

Abstract: Visual acuity and common medical examination did not distinguish convicted older drivers with crashes or other moving violations from controls. There was evidence that even mild cognitive impairment contributed to the risk of losing a driving license because of crashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 23 publications
(29 reference statements)
3
73
0
1
Order By: Relevance
“…Considerable research has shown that visuospatial ability measures are strongly correlated with driving ability (Reger et al, 2004). Concerning the visuospatial tasks included on the ACE-R, a poor pentagon design (copying of overlapping pentagons, from the MMSE) was predictive of self-reported driving difficulties (Gallo et al, 1999) and automobile crashes and moving violations (Marottoli et al, 1994), copying a cube was a strong predictor of crashes (Johansson et al, 1996), and clock drawing was predictive of real (De Raedt and Ponjaert-Kristoffersen, 2001) and simulated driving tasks (Freund et al, 2008) in active older drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has shown that visuospatial ability measures are strongly correlated with driving ability (Reger et al, 2004). Concerning the visuospatial tasks included on the ACE-R, a poor pentagon design (copying of overlapping pentagons, from the MMSE) was predictive of self-reported driving difficulties (Gallo et al, 1999) and automobile crashes and moving violations (Marottoli et al, 1994), copying a cube was a strong predictor of crashes (Johansson et al, 1996), and clock drawing was predictive of real (De Raedt and Ponjaert-Kristoffersen, 2001) and simulated driving tasks (Freund et al, 2008) in active older drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it comprises an MMSE score and sub-scores in five cognitive domains, which could provide qualitative and discriminative data regarding the patient's driving-related cognitive profile. Thirdly, the ACE-R may provide some discriminating value for driving ability, as it includes tasks that are similar to those previously associated with driving measures (cf., De Raedt and Ponjaert-Kristoffersen, 2001;Johansson et al, 1996;Marottoli et al, 1994). Finally, the ACE-R is a brief, inexpensive, and easily administered tool.…”
Section: Introductionmentioning
confidence: 99%
“…In a casecontrol study of older health maintenance organization members who were injured in state-recorded motor vehicle crashes, Koepsell and colleagues noted a similarly marginal association of crashing with falls (OR 1.4; 95% CI 0.9-2.4) (1994). Although the fall crash association is weak, several studies document highly similar, if not identical, risk factors for falls and crashes in the elderly [Tinetti et al 1988, Nevitt et al 1989, Sims et al 1998, Fitten et al 1995, Foley et al 1995, Johansson et al 1996Koepsell et al 1994, Marottoli et al 1994. For example, sedative use, depression and cognitive impairment, among others, have been implicated in these events [Tinetti et al 1988and1995, Hemmelgarn et al 1997, Sims et al 1998, Fitten et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptible older adults consistently demonstrate multiple impairments due to the effects of medications, chronic medical conditions, affective disorders, and visual and cognitive dysfunction [Tinetti et al 1988, Nevitt et al 1989, Sims et al 1998, Fitten et al 1995, Foley et al 1995, Johansson et al 1996Koepsell et al 1994, Marottoli et al 1994.…”
mentioning
confidence: 99%
“…Health concerns linked to unsafe driving in older drivers include chronic physical conditions (Dobbs, Caprio Triscott, & McCraken, 2004;Marottoli, Cooney, Wagner, Doucette, & Tinetti, 1994), visual attention and processing deficits (Ball & Owsley, 1991, 1996, and age-related cognitive decline and dementia (Cooper, Tallman, Tuokko, & Beattie, 1993;Dobbs, Heller, & Schopflocher, 1998;Johansson et al, 1996;McKnight & McKnight, 1999). As the percentage of older drivers in the population increases it is becoming increasingly important to have reliable and valid assessment tools to assess driving ability in this group.…”
Section: Introductionmentioning
confidence: 99%